Pengaruh Terapi Butterfly Hug terhadap Tingkat Kecemasan dalam Penyusunan Karya Tulis Ilmiah pada Mahasiswa Keperawatan Universitas Abulyatama - Widia Santri Telaumbanua; Nurul Sakdah; Yuli Zuhkrina (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Final-year students often experience anxiety while preparing their scientific papers, which can interfere with academic performance and psychological well-being. This condition generally arises from the pressure of completing final assignments, high academic demands, limited time, and fear of failure in meeting graduation requirements. One non-pharmacological approach that can be used to reduce this anxiety is Butterfly Hug therapy. Butterfly Hug is a simple self-regulation relaxation technique involving gentle, alternating taps on the chest and shoulder area, designed to stimulate the body’s calming response system. This technique is known to help individuals achieve relaxation, improve concentration, and maintain emotional stability during stressful situations. The purpose of this study was to examine the effect of Butterfly Hug therapy on students’ anxiety levels during the preparation of their scientific papers. The study used a quasi-experimental design with a one-group pretest–posttest approach. The sample consisted of 15 students selected through purposive sampling based on inclusion criteria. Data were collected using the Zung Self-Rating Anxiety Scale (Z-SAS). The intervention was conducted for three consecutive days, with each session lasting 10 minutes. The study was carried out from June 16–20, 2025 at the Diploma III Nursing Program, Faculty of Health Sciences, Abulyatama University, Aceh Besar. Data were analyzed using the Wilcoxon signed-rank test. The results showed a significant decrease in anxiety levels with a p-value of 0.002 (p < 0.05), indicating that Butterfly Hug therapy is effective in reducing student anxiety.